Delivery Systems for In Vivo use of Nucleic Acid Drugs - Resende R.R; Torres H.A.M; Yuahasi K.K; Majumder P; Ulrich H (AboutScience Srl, 2007)
The notorious biotechnological advance of the last few decades has allowed the development of experimental methods for understanding molecular mechanisms of genes and new therapeutic approaches. Gene therapy is maturing into a viable, practical method with the potential to cure a variety of human illnesses. Some nucleic-acid-based drugs are now available for controlling the progression of genetic diseases by inhibiting gene expression or the activity of their gene products. New therapeutic strategies employ a wide range of molecular tools such as bacterial plasmids containing transgenic inserts, RNA interference aptamers. A nucleic-acid based constitution confers a lower immunogenic potential and as result of the high stringency selection of large molecular variety, these drugs have high affi nity and selectivity for their targets. However, nucleic acids have poor biostability thus requiring chemical modifications and delivery systems to maintain their activity and ease their cellular internalization. This review discusses some of the mechanisms of action and the application of therapies based on nucleic acids such as aptamers and RNA interference as well as platforms for cellular uptake and intracellular delivery of therapeutic oligonucleotides and their trade-offs.